Isolation and Characterization of Pathogenic Bacteria from the Imported Artemia cysts in Bangladesh - Sultana, Sadia; Basak, Sushmita; Rahim, Samiur; Nawer, Poushali; Hoq, Md Mozammel; Naser, M Niamul; Akhter, Marufa Zerin; Karim, Muhammad Manjurul; Khan, Shakila Nargis (Bangladesh Journal of Microbiology, 2025)
Dormant cysts of brine shrimp (Artemia) are exclusively imported as a feed source for aquaculture industries in Bangladesh. Despite their high nutritional value, the potential introduction of exotic bacterial flora upon hatching is a growing concern. This study characterizes the bacterial community associated with commonly used Artemia cysts in Bangladesh and assesses their pathogenic potential following the current hatchery protocol. Using culture-based methods, 33 bacterial strains were isolated from encapsulated cysts post-hatching under gnotobiotic conditions. Through subsequent biochemical and 16S rRNA gene-based sequencing, 21 bacterial strains from different origins were identified as belonging to the genera Pseudomonas (n=9), Klebsiella (n=3), Enterobacter (n=4), Ralstonia (n=1), Aeromonas (n=1), and Vibrio (n=3). All 21 isolates exhibited á-hemolytic (n=8) and â-hemolytic (n=13) activities on blood agar, indicating their pathogenicity. Six of the isolated bacteria (one each from the identified genus) exhibited significant casein-protease activity and caused significant mortality in Artemia nauplii, with LD50 values ranging from 6.1 x 108 CFU/mL to 9.7 x 108 CFU/mL. The presence of these pathogenic bacteria in Artemia cysts suggests a potential biohazard, warranting their evaluation before introduction into hatcheries in Bangladesh. Bangla. J. Microbiol. 2025, Vol. 41, P: 1-8